2022
DOI: 10.3389/fvets.2022.921406
|View full text |Cite
|
Sign up to set email alerts
|

Arginine Regulates Zygotic Genome Activation in Porcine Embryos Under Nutrition Restriction

Abstract: Arginine has a positive effect on pre-implantation development in pigs. However, the exact mechanism by which arginine promotes embryonic development is undefined. Here, single-cell RNA sequencing technology was applied to porcine in vivo pre-implantation embryos from the zygote to morula stage, it was found that that the expression of arginine metabolism-related genes clearly changed from the 2-cell stage to the 4-cell stage, when zygotic genome activation (ZGA) occurs in porcine embryos. Further analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 93 publications
1
0
0
Order By: Relevance
“…Among these DEGs, the majority were transcribed from the embryonic genome or consisted of mixed maternal/embryonic transcripts. It is in agreement with studies using animal models, where it has been shown that the culture environment influences the maternal-to-embryonic transition, which itself influences the maternal transcript clearance ( Tesfaye et al, 2004 ; Zhang et al, 2022 ). A total of 19 of these DEGs could have a key role in early development, based not only on their dynamic expression changes across development but also on their association with GO terms related to essential developmental pathways, and were mostly upregulated in Ferticult.…”
Section: Discussionsupporting
confidence: 91%
“…Among these DEGs, the majority were transcribed from the embryonic genome or consisted of mixed maternal/embryonic transcripts. It is in agreement with studies using animal models, where it has been shown that the culture environment influences the maternal-to-embryonic transition, which itself influences the maternal transcript clearance ( Tesfaye et al, 2004 ; Zhang et al, 2022 ). A total of 19 of these DEGs could have a key role in early development, based not only on their dynamic expression changes across development but also on their association with GO terms related to essential developmental pathways, and were mostly upregulated in Ferticult.…”
Section: Discussionsupporting
confidence: 91%